Syngonanthus nitens Bong. (Rhul.)-loaded nanostructured system for Vulvovaginal candidiasis treatment - dos Santos Ramos, Matheus Aparecido [UNESP]; de Toledo, Luciani Gaspar [UNESP]; Fioramonti Calixto, Giovana Maria [UNESP]; Bonifácio, Bruna Vidal [UNESP]; de Freitas Araújo, Marcelo Gonzaga; dos Santos, Lourdes Campaner [UNESP]; de Almeida, Margarete Teresa Gottardo; Chorilli, Marlus [UNESP]; Bauab, Taís Maria [UNESP] (MDPI, 2016)
Herbal-loaded drug delivery nanotechnological systems have been extensively studied recently. The antimicrobial activity of medicinal plants has shown better pharmacological action when such plants are loaded into a drug delivery system than when they are not loaded. Syngonanthus nitens Bong. (Rhul.) belongs to the Eriocaulaceae family and presents antiulcerogenic, antioxidant, antibacterial, and antifungal activity. The aim of this study was to evaluate the antifungal activity of Syngonanthus nitens (S. nitens) extract that was not loaded (E) or loaded (SE) into a liquid crystal precursor system (S) for the treatment of vulvovaginal candidiasis (VVC) with Candida albicans. The minimal inhibitory concentration (MIC) was determined by the microdilution technique. Additionally, we performed hyphae inhibition and biofilm tests. Finally, experimental candidiasis was evaluated in in vivo models with Wistar female rats. The results showed effective antifungal activity after incorporation into S for all strains tested, with MICs ranging from 31.2 to 62.5 μg/mL. Microscopic observation of SE revealed an absence of filamentous cells 24 h of exposure to a concentration of 31.2 μg/mL. E demonstrated no effective action against biofilms, though SE showed inhibition against biofilms of all strains. In the in vivo experiment, SE was effective in the treatment of infection after only two days of treatment and was more effective than E and amphotericin B. The S. nitens is active against Candida albicans (C. albicans) and the antifungal potential is being enhanced after incorporation into liquid crystal precursor systems (LCPS). These findings represent a promising application of SE in the treatment of VVC.
Keywords: Candida albicans; Liquid crystal precursor system; Syngonanthus nitens; Therapeutic treatment; Vulvovaginal candidiasis